Bulbophyllum sondangii (Orchidaceae), a new species from Da Lat Plateau, southern Vietnam - Dang, Minh Quan; Averyanov, Leonid V.; Maisak, Tatiana V.; Nguyen, Quoc Bao; Bui, van Huong; Tu, Bao Ngan; Nguyen, van Canh; Truong, Ba Vuong (Phytotaxa, 2023)
A new species of Bulbophyllum (Orchidaceae), named as B. sondangii discovered in Da Lat Plateau (Da Lat Town area, Lam Dong Province of southern Vietnam) is described and illustrated. The new species is similar to B. andersonii and B. trongsaense, but can be distinguished by a short seta at the apex of median sepal and petals; almost entire margin of petals except the fimbriate apex; lip with auricles at base; and stelidia apiculate at apex. The paper presents the taxonomical description, data on distribution, ecology, phenology and conservation status, as well as notes and the comparison of the newly described plant with morphologically similar species.